Percutaneous Trigeminal Stimulation for Intractable Facial Pain: A Case Series. (18th December 2021) - Texakalidis, Pavlos; Tora, Muhibullah S; McMahon, J Tanner; Greven, Alexander; Anthony, Casey L; Nagarajan, Purva; Campbell, Melissa; Boulis, Nicholas M
Graphical Abstract: